Multiple sclerosis self-management model: Personal and contextual requirements for successful self-management. Issue 5 (May 2019) - Ghahari, Setareh; Forwell, Susan J.; Suto, Melinda J.; Morassaei, Sara
Highlights: Self-management is an integral part of managing life with multiple sclerosis (MS). Using ground theory, a self-management model was developed from an MS perspective. The model includes 6 person & 3 contextual strategies that can be used concurrently. Abstract: Objective: To explore self-management strategies used by people with multiple sclerosis (MS) with aim of developing a MS self-management model. Methods: A grounded theory approach guided development of a MS self-management model. Eighteen individuals living with MS for three or more years and self-identifying as successfully managing their MS were interviewed twice using semi-structured face-to-face or telephone interviews six months apart. Demographic and disease characteristics were descriptively analyzed. Field notes and interview data were qualitatively analyzed to identify concepts and categories. Results: The emerging model revealed six person-related categories describing self-management strategies: adjusting outlook, managing stress, managing symptoms, healthy lifestyle, effective communication, and setting priorities and planning. Three context-related categories that required successful navigation for self-management were also identified: physical environment, personal social network, and community services and resources. Conclusions: The emerging self-management model that is grounded in the perspective of people with MS includes person and context-related strategies that can be used concurrently to guide self-management in the variety of challenges experienced by people with MS. Practical Implications: A self-management model of MS is useful to service providers, health professionals, advocacy organizations and people with MS to draw upon an organized and comprehensive approach to self-management.